(BaSr)2SiO4:Eu2+ nanorods with enhanced luminescence properties as green-emitting phosphors for white LED applications. (July 2017) - Pavitra, E.; Seeta Rama Raju, G.; Oh, Ju-hyun; Krishna Bharat, L.; Jeong, Jung Hyun; Huh, Yun Suk; Yu, Jae Su
Abstract: To meet the requirements of warm white light-emitting diodes (WLEDs) with extreme thermal stability, high color rendering index and low color temperature, which is equivalent to natural sunlight, we need to develop novel phosphor materials that can efficiently absorb excitation energy from near-ultraviolet (NUV) LEDs and produce desired visible emissions. The Sr 2+ and Eu 2+ ions co-activated Ba2 SiO4 ((BaSr)Si:Eu 2+ ) green-emitting nanophopshors for NUV or blue excitation-based WLEDs are reported. After annealing at 1300 °C, the X-ray diffraction patterns established the pure orthorhombic phase of (BaSr)Si:Eu 2+ nanophosphors. The evolution of (BaSr)Si:Eu 2+ nanorods from the surface of the sub-micron sized (BaSr)Si:Eu 2+ particles showed a tremendous effect on the luminescent properties by enhancing the transmittance of the (BaSr)Si:Eu 2+ nanophosphor. The incorporation of Sr 2+ ions along with Eu 2+ ions into the Ba 2+ sites, the emission intensity was increased, and also the quantum efficiency was enhanced from 47 to 59%. Upon excitation at 370 nm, the Ba2 SiO4 :Eu 2+ phosphor exhibited a bluish-green emission while the yellowish-green emission was revealed by the (BaSr)Si:Eu 2+ nanophosphor. The thermal stability of the (BaSr)Si:Eu 2+ nanophosphor was verified at elevated temperatures and the activation energy for thermal quenching was found to be 0.38 eV. When the (BaSr)Si:Eu 2+ nanophosphor was coated on a NUV LED chip, the enriched green emission was observed by increasing the input current from 100 to 250 mA. The (BaSr)Si:Eu 2+ is expected to be a promising green-emitting phosphor material for the fabrication of NUV or blue excitation-based warm WLEDs for general illumination. Graphical abstract: Highlights: Facile sol-gel synthesis method is reported for the Ba2 SiO4 related materials. Crystallization, dissolution and recrystallization occur during annealing process. Synthesized nanorods induce the enhancement in luminescent properties.